Improving Students’ English Vocabulary Mastery Through Interactive Classroom Activities - Amellia Amellia; Tiyas Saputri (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
Vocabulary is crucial in learning a language. It helps students understand things, talk to each other, read books, and write stories. Many students struggle to learn new English words. This is because they don't use English much, don't practice enough, and the teaching methods aren't very engaging. These problems make it difficult for students to learn words, which means they lack confidence and don't participate as much in English class. This study examines how classroom activities can help students learn English words. Researchers examined activities such as playing word games, talking in groups, telling stories, pretending to be someone, and engaging in fun exercises. This study was conducted at SDN Kenjeran 248 Surabaya, with third-grade students. Researchers wanted to make the classroom a fun place to learn. Researchers found that some students lacked basic vocabulary such as sweeping, writing, reading, and so on. Researchers will conduct classroom activities that can help students learn words. When students do fun things and work together, they want to learn more and participate more. They remember new words more easily. So, doing fun things in class is a way to help students learn new words and make learning English more fun and engaging.